ZDHHC3 as a Risk and Mortality Marker for Breast Cancer in African American Women. (12th December 2017) - Kinney, Nick; Varghese, Robin T; Anandakrishnan, Ramu; Garner, Harold R "Skip"
African American woman are 43% more likely to die from breast cancer than white women and have increased the risk of tumor recurrence despite lower incidence. We investigate variations in microsatellite genomic regions—a type of repetitive DNA—and possible links to the breast cancer mortality gap. We screen 33 854 microsatellites in germline DNA of African American women with and without breast cancer: 4 are statistically significant. These are located in the 3′ UTR (untranslated region) of gene ZDHHC3, an intron of transcribed pseudogene INTS4L1, an intron of ribosomal gene RNA5-8S5, and an intergenic region of chromosome 16. The marker in ZDHHC3 is interesting for 3 reasons: (a) the ZDHHC3 gene is located in region 3p21 which has already been linked to early invasive breast cancer, (b) the Kaplan-Meier estimator demonstrates that ZDHHC3 alterations are associated with poor breast cancer survival in all racial/ethnic groups combined, and (c) data from cBioPortal suggest that ZDHHC3 messenger RNA expression is significantly lower in African Americans compared with whites. These independent lines of evidence make ZDHHC3 a candidate for further investigation.